2016
DOI: 10.1111/jace.14214
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Interatomic Bonding in Controlling the Mechanical Properties of Calcium Silicate Hydrates

Abstract: Calcium silicate hydrate (C-S-H) is the most important phase of hydrated cement gel which is the key material in construction industry. It is well accepted that hardened cement paste consists of either poorly crystalline or completely disordered phases. Although a myriad of speculative atomistic models of disordered C-S-H have been proposed, the fundamental basis of structure-property relationships remain elusive. This study focuses upon the correlations between mechanical properties and electronic structure b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…At nanoscale (smaller than 10 nm), the structural water is found to be a scaffolding component enhancing mechanical properties of C-S-H nanoparticles13. On the contrary, the sub-micron mechanical properties (characterized by nanoindentation with a detecting window of around 500 nm) are lower when water content increases24.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…At nanoscale (smaller than 10 nm), the structural water is found to be a scaffolding component enhancing mechanical properties of C-S-H nanoparticles13. On the contrary, the sub-micron mechanical properties (characterized by nanoindentation with a detecting window of around 500 nm) are lower when water content increases24.…”
Section: Discussionmentioning
confidence: 97%
“…By performing molecular dynamics simulation and further numerical analysis, one can measure material properties of C-S-H nanocrystals and adhesion strength between C-S-H layers101112. The internal structural water is found to be a scaffolding component that enhances the mechanical properties of C-S-H13. The Young’s modulus of C-S-H nanoparticles is around 70 GPa14, higher than that of conventional concrete.…”
mentioning
confidence: 99%
“…In fact, the BO is a single well-defined descriptor irrespective of the nature of the bonding, be it ionic, covalent, metallic, H-bonding, or non-directional bonding as in BMGs. The use of BO and TBOD in different materials systems has been demonstrated in several recent publications[62][63][64][65][66][67][68][69][70][71][72]. Results and Discussion3.1 Structure and topology of Vit-1 modelsThe total pair distribution function (PDF) G(r) of our model for Zr 41.2 Ti 13.8 C 12.5 Ni 10 Be 22.5 is shown inFigure 2(a).…”
mentioning
confidence: 88%
“…The plot of BO vs BL is shown in Figure 6(a) From the BO values for all interatomic pairs, we can obtain the total bond order for that pair of atoms by adding them together and normalize by the volume of the cell, we have the bond order density (BOD). When the BOD of all pairs are added, we have the total BOD (TBOD) which is a single quantum mechanical metric best describe the interatomic cohesion of a crystal or a glass in the present case [67,69]. The use of TBOD in characterizing different type of materials is a novel concept that we advocate since the volume of the system is part of the metric.…”
Section: Electronic Structure and Bondingmentioning
confidence: 99%
“…Due to the complexity of cementitious materials, the behavior of C‐S‐H at these length scales cannot be easily probed through experiments and requires atomistic simulations. Models are typically based on either idealized crystalline analogs of C‐S‐H or by manipulating an initially crystalline structure to obtain a defective C‐S‐H model . Simulations have found that under pure shear loading, the composite interface allows for strain localization that controls the strength of the atomistic structure .…”
Section: Introductionmentioning
confidence: 99%